Silane catecholates: versatile tools for self-assembled dynamic covalent bond chemistry. Issue 43 (8th May 2019) - Kawakami, Yoshiteru; Ogishima, Tsuyoshi; Kawara, Tomoki; Yamauchi, Shota; Okamoto, Kazuhiko; Nikaido, Singo; Souma, Daiki; Jin, Ren-Hua; Kabe, Yoshio
Abstract : Shape-persistent macrocycles and 3D nanocages have been prepared in one-pot under MeCN-promoted dynamic covalent bond conditions starting from silane catecholates, whose structures were confirmed by X-ray crystallography. Abstract : Shape-persistent macrocycles and 3D nanocages have been prepared in one-pot under MeCN-promoted dynamic covalent bond conditions starting from silane catecholates, whose structures were confirmed by X-ray crystallography. Cation-exchange reactions of macrocycles and nanocages were performed along with the encapsulation of ammonium ions within the cavity of an anionic macrocycle and a tetrahedral nanocage.